Towards a Green Workforce: Assessing Green Job Preparation in Panamanian and Costa Rican Universities - Ulrich,Julius (2023)
The triple planetary crisis exerts high pressure on countries to transform their current economic system. The transition to a green economy is not only necessary to ensure sustainable development but also essential for countries to remain economically competitive. The neighbouring countries Panama and Costa Rica are both facing significant challenges under the green transition, despite their different growth and sustainability strategies. The lack of a properly trained workforce and underdeveloped green skills are significantly slowing down the green transition. To meet the growing demand for green high-skilled labour in Panama and Costa Rica, universities must incorporate green skills concepts in their institutional strategy. By enhancing UNEPs Education for Green Jobs Framework with additional Latin American specific aspects, the author developed the Education for Green Jobs in Latin America Framework. Guided by the theoretical framework, this study explores the current preparation of university students in Panama and Costa Rica to enter the green jobs market. The qualitative multiple case study comparison shows the current offerings of three universities in Panama and three universities in Costa Rica and how they include green job preparation in their curricula and extra-curricular activities. Further, possible areas for improvement are identified through interviews with thematic experts, green jobs representatives and students. In total, 26 interviews, 10 focus group discussions and a thorough document analysis were conducted. Findings suggest that universities in Panama and Costa Rica are willing to support the green transition and incorporate green job preparation concepts in their degrees. However, there are still significant gaps and a lack of coherence in their actions. A clear need for widespread and strategic transformations has been identified. Possible interventions are suggested in the areas of holistic sustainability strategy and approach, knowledge enhancement, skills and competency development and job opportunities. The findings herein support theoretical expectations and provide new perspectives on university students green jobs preparation.
Keywords: Panama; Costa Rica; Universities; Education for Green Jobs; Education for Sustainable Development; Green Transition; Green Skills; Triple Planetary Crises